FRI0418 Male Gender but Not HLA-B27 Positivity or Occurrence of Uveitis as Severity Prognostic Factor in Sardinian Ankylosing Spondylitis Patients. (15th July 2016) - Porru, G.; Marras, M.; Piga, M.; Floris, A.; Ibba, V.; Marcia, S.; Mathieu, A.; Cauli, A.
Abstract : Background: Susceptibility to develop Ankylosing Spondylitis (AS) is strongly influenced by the presence of the HLA-B27 gene, but much less defined are prognostic factors which may predict erosions and new bone formation lesions leading to organic damage and spinal ankylosis. Given the differences in the genetic background among populations, it is conceivable that prognostic factors may also mirror this genetic variability. Objectives: The main aim was to study, in a cohort from the genetic isolate of Sardinia, possible clinical prognostic factors which may predict a more severe spinal damage as assessed by a validated radiological score. Methods: Medical history, clinical and radiological data from 100 consecutive patients with AS were collected in a tertiary referral rheumatology clinic; 73 were male (mean age 44.9±10.5; disease duration 18.3±10.6 years) and 27 females (mean age 44.5±13.0; disease duration 14.9±8.9 years). Radiological cervical and lumbar spinal assessment was performed by means of the mSASSS index, sacro-iliac joints were evaluated according to New York criteria. Rx films were blindly assessed by an expert rheumatologist (GP) and by a radiologist (MM). Results were expressed as mean or median, according to numerical distribution. Statistical analysis was performed by means of GraphPad Prism software according to Mann-Whitney and Spearman's tests. Results: Analysis of data revealed a good inter-observer and intra-observer agreement 0.94 (0.91–0.97) and 0, 95 (0, 88–0, 96), respectively. Radiological spinal and sacroiliac joint severity indexes were positively correlated with patient's age and disease duration (p<0.0001). mSASSS was shown to correlate with BASDAI, BASFI and BASMI (p=0.002, p<0.0001 and p<0.0001, respectively) while New York sacroiliac score was found to correlate with BASMI only (p<0.0001). Radiological spinal involvement resulted more severe in male vs female patients (mSASSS 8; 3.5–33 vs 4; 1–10, p=0, 008), mainly due to a greater involvement of the lumbar tract with similar cervical severity. These objective data are in contrast to clinical metrology and patient reported outcomes which showed similar BASMI and BASFI scores and lower BASDAI (2.5±2.1 vs 3.9±2.3, p=0.02) in male versus female. Interestingly, the occurrence of an extra-articular feature such as acute anterior uveitis (AAU) did not result to be a severity prognostic factor (p=ns). Furthermore, it is noteworthy that no statistical differences were noted comparing HLA-B27 positive patients for radiological severity (mSASS 6.5; 2–19) vs HLA-B27 negative (mSASS 8.5; 2–45 p=ns), as well as for disease activity, functional and metrology indexes (BASDAI 2.8±2.3 vs 3.9±2.3; BASFI 2.7±2.6 vs 3.4±2.9; BASMI 2.3±2.4 vs 3.8±3.1; p=ns). Finally, mSASSS or sacroileiitis indexes were not correlated with anti-TNF treatment. Conclusions: In AS patients from the genetic isolate of Sardinia, male gender but not HLA-B27 positivity or occurrence of AAU is associated with a more severe radiological outcome. Disclosure of Interest: None declared